Species-dependent toxicity, accumulation, and subcellular partitioning of cadmium in combination with tetrabromobisphenol A in earthworms. (November 2018) - Chen, Xian; Gu, Xueyuan; Zhao, Xiaopeng; Ma, Xuan; Pan, Yanan; Wang, Xiaorong; Ji, Rong
Abstract: Cadmium (Cd) and tetrabromobisphenol A (TBBPA) are two ubiquitous pollutants in soils and are often found together at electronic waste recycling sites. In this study, their toxicity as well as the accumulation and subcellular partitioning of Cd were determined in two ecologically different earthworms Eisenia fetida and Metaphire guillelmi exposed for 14 days to Cd (1 mg kg −1 ) and TBBPA (10, 50, 100, and 500 mg kg −1 ) alone and in combination. In general, Cd-TBBPA co-exposure resulted in synergistic effects in terms of acute toxicity, growth inhibition, histopathological changes in body walls, and oxidative stress responses to earthworms, moreover, M. guillelmi showed higher sensitivity than E. fetida . Principal component analysis showed that the two earthworm species differed in their biomarker expression patterns. In addition, Cd accumulation was significantly ( P < 0.01) reduced in E. fetida co-exposed to TBBPA but significantly ( P < 0.05 and 0.01) enhanced in M. guillelmi . The difference in bioaccumulation between the two earthworm species may be made by their different exposure routes despite the decrease of Cd bioavailability (assessed by the diffusive gradients in thin films technique) in the soils. High doses of TBBPA also altered the subcellular distribution of Cd in the earthworms. These findings demonstrate the need to include more ecologically relevant earthworm species, represented in this study by M. guillelmi, in soil risk assessments of Cd and TBBPA co-exposure. Graphical abstract: Image 1 Highlights: M. guillelmi showed higher sensitivity than E. fetida to Cd and TBBPA co-exposure. The two earthworm species differed in the pattern of oxidative stress responses. TBBPA addition inhibited Cd uptake in E. fetida due to Cd bioavailability decrease. More Cd accumulated in M. guillelmi in the presence of TBBPA. The high dose of TBBPA altered Cd subcellular partitioning in earthworms. Abstract : Capsule : Metaphire guillelmi co-exposed to Cd and TBBPA displayed a higher sensitivity than Eisenia fetida and differed in its accumulation and subcellular partitioning of Cd.